Pesan Kampanye Penggunaan Sedotan Stainless Steel: Perspektif Theory of Planned Behavior - Dede Kurniyawan (Mediator: Jurnal Komunikasi, 2023)
Tackling climate change is the 13th goal in the Sustainable Development Goals (SDGs). One of the simple actions that can be taken in order to prevent the issue of climate change is the use of environmentally friendly straws, specifically the use of stainless steel straws. In order for the public to know about the issue of climate change, social media has an important role. This study aims to see the effect of social media exposure related to climate change issues on behavior to use stainless steel straws. In addition, this study uses predictors of the Theory of Planned Behavior, namely attitudes, subjective norms, and Perceived Behavioral Control (PBC). By using Structural Equation Modeling (SEM), the results of the study show that attitudes, subjective norms, and Perceived Behavioral Control (PBC) directly influence an intentions and indirectly influence the behavior of using stainless steel straws. Another finding is that exposure to social media related to climate change issues owned by family and close friends also has a direct positive effect on attitudes, subjective norms, Perceived Behavioral Control, and behavioral intentions, which in turn have a positive indirect effect on the behavior of using stainless steel straws.